1990
DOI: 10.1002/1097-0355(199022)11:2<175::aid-imhj2280110208>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

A curvilinear relationship between maternal vocal stimulation and three-month-olds' cognitive processing: A cross-cultural phenomenon

Abstract: This article presents data from four independent studies on the relationship between quantity of maternal vocal stimulation during naturalistic conditions and 3‐month‐old infants' cognitive processing, as assessed by the infants' differential vocal responsiveness (DVR) to their mother versus a female stranger. In two of the studies, the subjects were full‐term American infants whose parents came from a wide socio‐educational and ethnic background. In the third study, the subjects were low‐risk preterm infants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
0
19
0
1
Order By: Relevance
“…Other research has converged on such a model, in which distress biases the system toward both heightened interactive contingency (in some modalities) and lowered (in others) (Belsky, Rovine, & Taylor, 1984; Hane, Feldstein, & Dernetz, 2003; Leyendecker, Lamb, Fracasso, Scholmerich, & Larson, 1997; Lewis & Feiring, 1989; Malatesta et al, 1989; Roe, Roe, Drivas, & Bronstein, 1990). …”
Section: The Meaning Of Higher and Lower Degrees Of Self- And Interacmentioning
confidence: 99%
“…Other research has converged on such a model, in which distress biases the system toward both heightened interactive contingency (in some modalities) and lowered (in others) (Belsky, Rovine, & Taylor, 1984; Hane, Feldstein, & Dernetz, 2003; Leyendecker, Lamb, Fracasso, Scholmerich, & Larson, 1997; Lewis & Feiring, 1989; Malatesta et al, 1989; Roe, Roe, Drivas, & Bronstein, 1990). …”
Section: The Meaning Of Higher and Lower Degrees Of Self- And Interacmentioning
confidence: 99%
“…Sander (1995) reported that relatively more "loosely coupled" (midrange) mother-infant dyads were more resilient whereas in more tightly coupled dyads, any disruption may shatter the system. Roe, Roe, Drivas, and Bronstein (1990) found that only moderately talkative mothers both initiated vocalizations and allowed their infants to do the same; these infants vocalized preferentially to their mothers (vs. strangers), and at 3 and 5 years, exhibited higher cognitive scores. Across 4, 8, and 12 months, Leyendecker et al (1997) found that secure dyads showed midrange degrees of contingency whereas insecure dyads received higher or lower scores.…”
Section: The Optimum Midrange Model Of Interactive Regulationmentioning
confidence: 99%
“…Using the same procedure as in the Roe et al (1990) study, the mothers of the 147 subjects were rank-ordered in accordance with the quantity of the maternal vocal stimulation to their infants during the 30-minute naturalistic sessions. Using the same procedure as in the Roe et al (1990) study, the mothers of the 147 subjects were rank-ordered in accordance with the quantity of the maternal vocal stimulation to their infants during the 30-minute naturalistic sessions.…”
Section: Subjectsmentioning
confidence: 99%
“…Quantity of maternal vocal stimulation during naturalistic sessions. Using the same procedure as in the Roe et al (1990) study, the mothers of the 147 subjects were rank-ordered in accordance with the quantity of the maternal vocal stimulation to their infants during the 30-minute naturalistic sessions. Subsequently, they were separated into Low, Middle, and High Mother Naturalistic Vocalization (MNV) groups, each containing 49 Subjects.…”
Section: Subjectsmentioning
confidence: 99%